Central and Eastern Europe's Response to Trafficking - Maciej Witold Bernasiewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: The text characterizes the phenomenon of human trafficking in three countries: Bulgaria, Romania, and Poland. It was decided to describe ways to combat this phenomenon using the example of Poland. Research Aim: The goal of study was to submit a short report on the general situation in the field of human trafficking in selected countries of Central and Eastern Europe. Evidence-based Facts: Central and Eastern Europe is the origin, transfer, and destination for victims of human trafficking. While in Bulgaria or Romania sexual exploitation is predominant among the victims identified, forced labour is predominant in Poland. Summary: Help for victims of human trafficking is largely based on the activities of non-governmental organizations, and the state is left only to prosecute this crime. Poland considered this outsourcing of assistance to victims more effective than building a public assistance system.